2022
DOI: 10.1155/2022/3928717
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Consumption Pattern, and Adverse Effects of Energy Drinks among Asian Population: A Cross-Sectional Analysis from Malaysia

Abstract: Background. The frequent expansion of the energy drinks (EDs) market has caused an extensive increase in the consumption of EDs, especially among younger populations. However, the lack of knowledge on EDs and their perceived beneficial effects could lead to excessive EDs consumption, which is strongly associated with serious side effects. This study aimed to assess the knowledge and perceived beneficial effects of EDs consumers and determine the consumption patterns and side effects experienced by different ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…According to the results of this study, compared with nurses who did not consume energy drinks, nurses who consumed energy drinks tended to believe that “Energy drinks have an arousal effect” and “Energy drinks can replace coffee or soda.” These perceptions are consistent with the results showing the time of energy drink intake; notably, the nurses regularly consumed energy drinks that are similar to other beverages, such as coffee or soda, to study or work late at night. The results of this study are in agreement with those of the previous studies reporting energy drink consumption for fatigue reduction and maintenance of concentration and wakefulness (Bulut et al, 2014; Mohammed et al, 2022; Rooyen et al, 2021; Subaiea et al, 2019). Therefore, follow‐up research is necessary to investigate the reasons for a more positive perception of energy drinks, such as wakefulness and a reduction in fatigue, rather than a negative perception, such as palpitations and sleep disturbances.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to the results of this study, compared with nurses who did not consume energy drinks, nurses who consumed energy drinks tended to believe that “Energy drinks have an arousal effect” and “Energy drinks can replace coffee or soda.” These perceptions are consistent with the results showing the time of energy drink intake; notably, the nurses regularly consumed energy drinks that are similar to other beverages, such as coffee or soda, to study or work late at night. The results of this study are in agreement with those of the previous studies reporting energy drink consumption for fatigue reduction and maintenance of concentration and wakefulness (Bulut et al, 2014; Mohammed et al, 2022; Rooyen et al, 2021; Subaiea et al, 2019). Therefore, follow‐up research is necessary to investigate the reasons for a more positive perception of energy drinks, such as wakefulness and a reduction in fatigue, rather than a negative perception, such as palpitations and sleep disturbances.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that the proportion of nurses who consume energy drinks in the United States is 22.5% (Higbee et al, 2020), and 18.2% of Saudi adolescents and adults consume energy drinks each day (Subaiea et al, 2019). Another previous study from Malaysia showed that approximately 50% of the subjects consumed coffee in addition to energy drinks (Mohammed et al, 2022). Consuming coffee and tea in addition to energy drinks can lead to excessive caffeine intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Rakuten Insight's poll of 9340 participants, almost 50% of Malaysian respondents aged 25 to 34 years old consume energy-boosting drinks with high caffeine content. 4 Pharmacy students are one of the tough courses that have a packed schedule with assignments, exams, and socializing. 5 To be able to stay energetic throughout the day, caffeine becomes a part of the student's lives.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (2018) also recommend that college students be taught the potential health risks of EDs. Mohammed et al (2022) concluded that ED consumers did not know much about them. As a result, the Ministry of Health should pay attention to the major side effects that ED consumers experience, such as palpitations and nervousness, and raise awareness about them.…”
Section: Introductionmentioning
confidence: 99%